Technology Startups in Indonesia: Riding the Wave of Innovation and Investment - Iskandar , Deni (Sinergi International Journal of Economics, 2024)
The success and expansion of technology companies in Indonesia are examined in this study, with a particular emphasis on the role played by infrastructure, the entrepreneurial ecosystem, government assistance, innovation, and investment. A survey-based quantitative analysis was carried out on a sample of 226 technology startups from different industries. Partial Least Squares (PLS) and Structural Equation Modeling (SEM) were used to examine the connections between the previously listed components. The results show that government support, innovation, infrastructure, the entrepreneurial ecosystem, and investment are all significantly positively correlated. Startups' capacity to attract investment is positively impacted by improved infrastructure, a friendly entrepreneurial ecosystem, efficient government policies, and an emphasis on innovation. The significance of creating a favorable atmosphere for innovation and startup development in Indonesia is highlighted by these findings, providing crucial insights for policy-makers and investors in fostering a thriving tech sector.